1996
DOI: 10.1177/107769909607300306
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the News: A Conceptual and Methodological Framework

Abstract: Content diversity, a journalistic tenet that addresses the concept of the marketplace of ideas, is a fundamental dimension of news diversity. This content analysis of newspaper articles measures the difference between diversity of ideas (content) and diversity of sources, two constructs that others have assumed are highly correlated. The findings indicate that the difference is substantial. Although content diversity may sometimes accompany source diversity, it is fallacious to assume that one ensures the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 0 publications
1
74
0
1
Order By: Relevance
“…Similarly, journalists and the public agree that diversity efforts in the newsroom will produce beneficial results for the community (Gross, Craft, Cameron, & Antecol, 2002). On the business side, a diverse newsroom might favorably influence the newspapers' reputation, resulting in increased circulation (Voakes, Kapfer, Kurpius, & Chern, 1996). Owners interested in the profit margin are well aware that they must cover minority issues to attract minority readers (Ankney & Procopio, 2003;Brislin & Williams, 1996;Gross, Curtin, & Cameron, 2001).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Similarly, journalists and the public agree that diversity efforts in the newsroom will produce beneficial results for the community (Gross, Craft, Cameron, & Antecol, 2002). On the business side, a diverse newsroom might favorably influence the newspapers' reputation, resulting in increased circulation (Voakes, Kapfer, Kurpius, & Chern, 1996). Owners interested in the profit margin are well aware that they must cover minority issues to attract minority readers (Ankney & Procopio, 2003;Brislin & Williams, 1996;Gross, Curtin, & Cameron, 2001).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Only a handful of studies have addressed the impact of media concentration and types of ownership on the actual news content. Some of these have addressed the issue of content diversity (Entman, 2006;Voakes, Kapfer, Kurpius, & Chern, 1996), but have not been able to establish any causal interference. While some studies show a reduction in media coverage diversity in the wake of mergers or acquisitions (Landry, 2011), other studies find stability, convergence and divergence in editorial content over time (Ho & Quinn, 2009).…”
Section: Concern 3: Towards Increasing Power Concentration and Decreamentioning
confidence: 99%
“…Voakes et al found that medium and small news organizations have a much larger percentage of wire copy on issues of statewide interest than larger ones. 7 And although people may turn to newspapers for local news first, national, international and state news are also in the top six among content category preferences for readers of all ages. 8 Although the Web in general can be a dubious source for trustworthy information, users do seem willing to turn to online newspapers for non-local stories of importance to them.…”
Section: Gate-keeper To a Post-modern World?mentioning
confidence: 99%